Clinico-etiological profile of neonates with neonatal hyperbilirubinmemia treated with double volume exchange transfusion - Mir, Naseer Y.; Irtika; Zaman, Bashir U. (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal hyperbilirubinemia continues to be the most common cause of hospital admissions and readmissions in the neonatal population worldwide and this pattern continues despite attempts to identify neonates at risk of pathological hyperbilirubinemia. The aim of the study was to determine the clinical profile and etiology in neonates who were treated with double volume exchange transfusion (DVET). Methods: This was a hospital based prospective observational study in neonates ≥35 weeks of gestation who were treated with DVET for severe hyperbilirubinemia in a tertiary care centre over a period of six months. Results: In our study 110 neonates with severe hyperbilirubinemia were treated with DVET. Majority of the neonates were males (59.1%). Lower segment caesarean section (LSCS) was the common mode of delivery observed in 66.4% of the study subjects. Rh incompatibility (36.4%) was the commonest cause of exchange transfusion followed by ABO incompatibility (20%). The mean age of neonates at admission and mean age at DVET in days were 4.03±2.46 and 4.25±2.44 respectively. The mean birth weight of neonates treated with DVET was found to be 2.81±0.57. The mean total serum bilirubin at pre-exchange and post exchange were 26.13±6.58 mg/dl and 11.63±3.24 mg/dl respectively. Conclusions: Rh incompatibility was the most common cause in neonates with severe hyperbilirubinemia requiring double volume exchange transfusion.